The stress kinase GCN2 does not mediate suppression of antitumor T cell responses by tryptophan catabolism in experimental melanomas - Sonner, Jana K.; Opitz, Christiane; Wick, Wolfgang; Platten, Michael (OncoImmunology, 2016)
Tryptophan metabolism is a key process that shapes the immunosuppressive tumor microenvironment. The two rate-limiting enzymes that mediate tryptophan depletion, indoleamine-2,3-dioxygenase (IDO) and tryptophan-2,3-dioxygenase (TDO), have moved into the focus of research and inhibitors targeting IDO and TDO have entered clinical trials. Local tryptophan depletion is generally viewed as the crucial immunosuppressive mechanism. In T cells, the kinase general control non-derepressible 2 (GCN2) has been identified as a molecular sensor of tryptophan deprivation. GCN2 activation by tryptophan depletion induces apoptosis and mitigates T cell proliferation. Here, we investigated whether GCN2 attenuates tumor rejection in experimental B16 melanoma using T cell-specific Gcn2 knockout mice. Our data demonstrate that GCN2 in T cells did not affect immunity to B16 tumors even when animals were treated with antibodies targeting cytotoxic T lymphocyte antigen-4 (CTLA4). GCN2-deficient gp100 TCR-transgenic T cells were equally effective as wild-type pmel T cells against gp100-expressing B16 melanomas after adoptive transfer and gp100 peptide vaccination. Even augmentation of tumoral tryptophan metabolism in B16 tumors by lentiviral overexpression of Tdo did not differentially affect GCN2-proficient vs. GCN2-deficient T cells in vivo. Importantly, GCN2 target genes were not upregulated in tumor-infiltrating T cells. MALDI-TOF MS imaging of B16 melanomas demonstrated maintenance of intratumoral tryptophan levels despite high tryptophan turnover, which prohibits a drop in tryptophan sufficient to activate GCN2 in tumor-infiltrating T cells. In conclusion, our results do not suggest that suppression of antitumor immune responses by tryptophan metabolism is driven by local tryptophan depletion and subsequent GCN2-mediated T cell anergy.